Haploidentical Stem Cell Transplant With Post-transplant Cyclophosphamide for Chediak-Higashi Syndrome: A Very Rare Case Report. Issue 7 (21st October 2021) - Sachdev, Mansi; Bansal, Minakshi; Chakraborty, Sohini; Hamal, Sushma; Bhargava, Rahul; Dua, Vikas
Abstract : Chediak-Higashi syndrome is a rare immunodeficiency disorder for which hematopoietic stem cell transplant (HSCT) is the only curative treatment option. HSCT only corrects the hematologic and immunologic manifestations of the disease but neurologic complications may still progress after transplant. Haploidentical HSCT (haplo-HSCT) has evolved as a feasible alternative for patients with primary immunodeficiency. More recently, there has been use of haplo-HSCT with post-transplant cyclophosphamide. However, only 4 cases of Chediak-Higashi syndrome have been reported using this approach. Here, the authors describe a case of a 17-month-old boy who was successfully treated by haplo-HSCT with reduced-toxicity conditioning (fludarabine/treosulfan/melphalan) and post-transplant cyclophosphamide.